Utilization Of Big Data In Business Analysis In Micro, Small And Medium Enterprises (MSME) In Order To Increase The Scale Of Economic Business In The Sumatra Region - Edi Suranta Tarigan; Wisnu Mawardi (UNIVED Press, 2024)
The purpose of this study is to analyze the potential and inhibiting factors in MSME businesses in North Sumatra in order to increase the economic scale of these businesses. This research uses a mixed method approach, combining quantitative and qualitative analysis. Secondary data was obtained from sources such as the Central Bureau of Statistics, the Office of Communication and Information, and Bank Indonesia. The quantitative approach was used to provide an overview of MSMEs and economic conditions in the region. The qualitative approach provides an in-depth understanding of the challenges, opportunities and factors affecting the development of MSME. The results revealed that MSME growth in North Sumatra Province still faces a number of challenges. MSME growth is not yet optimal, digital technology adaptation is limited, marketing strategies and product quality need to be improved, and access to capital is still an obstacle. Determinants such as product registration in ecatalogue, management training, increased utilization of information technology, improved product quality, and expanded market access were identified as important measures to improve MSME growth. This research shows that MSME in North Sumatra Province have the potential to contribute more to regional economic growth if the challenges faced can be overcome. Better marketing strategies, adaptation of digital technology, improvement of product quality, and expansion of market access can be key in improving the growth of MSME. Through the recommendations generated, it is expected that the government and businesses can design effective measures to support the sustainable growth of MSME and the regional economy in North Sumatra Province